Synthesis and NMR study of trimethylphosphine gold(i)-appended calix[8]arenes as precursors of gold nanoparticles. Issue 4 (15th January 2020) - Clément, Marie; Abdellah, Ibrahim; Ray, Priyanka; Martini, Cyril; Coppel, Yannick; Remita, Hynd; Lampre, Isabelle; Huc, Vincent
Abstract : In this paper, the synthesis of gold(i )-calix[8]arene complexes from benzyloxycalix[8]arene is reported as well as their radiolytic reduction leading to gold nanoparticles. Abstract : In this paper, the synthesis of gold(i )-calix[8]arene complexes from benzyloxycalix[8]arene used as a starting material is reported. 8 or 16 trimethylphosphine-gold(i ) are grafted to the calix[8] arene via a C4 alkane chain linker and a thiolate group. The formed gold(i )-complexes are studied by NMR spectroscopy. It is also shown that these complexes can act as both source of metal and stabilizing agent for the formation of gold nanoparticles as the radiolytic reduction of these complexes produces small monodisperse nanoparticles.